Digital entrepreneurship: bibliometric analysis on Scopus and Wos database - Frende Vega, María de los Ángeles; Vásquez Torres, Jayguer Dayan; García, Milagros del Carmen (Revista Venezolana de Gerencia, 2025)
This study analyzes the academic literature on entrepreneurship and new technologies through a bibliometric approach. A proprietary database of 3288 works was constructed by combining Web of Science (WoS) and SCOPUS, offering a broader perspective on the field. The results reveal a growing interest in digital entrepreneurship, particularly since 2017, with Technological Forecasting and Social Change emerging as the most impactful journal. Influential works by authors such as S. Nambisan highlight the transformative role of digital technologies in entrepreneurial ecosystems. Thematic analysis identifies digitalization, innovation, and business models as central "motor themes," emphasizing their importance in entrepreneurial research. This study underscores significant research gaps, providing valuable insights for entrepreneurs seeking innovation opportunities and for policymakers designing digital ecosystems to support sustainable ventures. Educational institutions are urged to integrate digital skills and entrepreneurship training to prepare future entrepreneurs. By jointly analyzing WoS and SCOPUS, this work addresses prior methodological limitations, offering a comprehensive contribution to the understanding of digital entrepreneurship. It provides actionable insights for stakeholders in academia, industry, and government, fostering further research and development in this evolving field.